Low gut microbiota diversity in early infancy precedes asthma at school age. Issue 6 (June 2014) - Abrahamsson, T. R.; Jakobsson, H. E.; Andersson, A. F.; Björkstén, B.; Engstrand, L.; Jenmalm, M. C.
Summary Background Low total diversity of the gut microbiota during the first year of life is associated with allergic diseases in infancy, but little is known how early microbial diversity is related to allergic disease later in school age. Objective To assess microbial diversity and characterize the dominant bacteria in stool during the first year of life in relation to the prevalence of different allergic diseases in school age, such as asthma, allergic rhinoconjunctivitis (ARC) and eczema. Methods The microbial diversity and composition was analysed with barcoded 16S rDNA 454 pyrosequencing in stool samples at 1 week, 1 month and 12 months of age in 47 infants which were subsequently assessed for allergic disease and skin prick test reactivity at 7 years of age (ClinicalTrials.gov ID NCT01285830). Results Children developing asthma (n = 8) had a lower diversity of the total microbiota than non‐asthmatic children at 1 week (P = 0.04) and 1 month (P = 0.003) of age, whereas allergic rhinoconjunctivitis (n = 13), eczema (n = 12) and positive skin prick reactivity (n = 14) at 7 years of age did not associate with the gut microbiota diversity. Neither was asthma associated with the microbiota composition later in infancy (at 12 months). Children having IgE‐associated eczema in infancy and subsequently developing asthma had lower microbial diversity than those that did not. There were no significant differences, however, in relative abundance of bacterial phyla and genera between children with or without allergic disease. Conclusion and Clinical Relevance Low total diversity of the gut microbiota during the first month of life was associated with asthma but not ARC in children at 7 years of age. Measures affecting microbial colonization of the infant during the first month of life may impact asthma development in childhood.